Ultrasonic guided wave nondestructive testing of anchorage quality of rebar resin bolt based on EMD-PCA - Kesong Fan; Ao Yan; Shaowei Liu; Can Zhang; Youliang Feng; Mengxiong Fu; Deyin He (Scientific Reports)
Abstract Currently, the ultrasonic guided wave inspection of the anchoring quality of rebar resin bolts in coal mine tunnels faces issues such as rapid signal energy attenuation, waveform superposition of reflected waves, and waveform complexity, making it difficult to effectively identify anchoring quality. Therefore, a method combining Empirical Mode Decomposition (EMD) with Principal Component Analysis (PCA) is proposed for processing and analyzing ultrasonic guided wave detection signals. This study employs numerical simulation combined with laboratory testing, selecting low-frequency guided waves at 50 kHz with lower attenuation as excitation signals to simulate the propagation process of ultrasonic guided waves through rebar resin bolt and surrounding anchorage media. Concurrently, an indoor nondestructive testing experimental platform was established to investigate signal propagation patterns across specimens with varying anchorage qualities. Finally, the EMD-PCA method was applied to process and analyze defect signals. Results demonstrate that this signal processing method can accurately identify the actual positions and lengths of anchorage defects, with discrepancies between numerical simulations and laboratory measurements remaining within 9.5%. For extended anchorage defects, the positioning error of defect locations is less than 2%. When defect interfaces approach the distal end of the anchorage, the IMF2 mode derived from EMD decomposition remains effective in extracting wave impedance difference interface reflections, thereby verifying the feasibility of applying the EMD-PCA signal processing method to ultrasonic guided wave nondestructive detection of defects in rebar resin bolts in coal mine tunnels.